Рядом с Пушкиным: Портреты кистью и пером: В 2 ч. (В. Д. Соколов) (1998)
На обл.: К 200-летию поэта Экземпляры: (20200327) / Инвентарный номер: 35788 / Цена: / Сис.шифр: 83.3(2Рос=Рус)1 / Авт.знак: С 59 / ББК: 83.3(2Рос=Рус)1